2018
DOI: 10.1111/een.12516
|View full text |Cite
|
Sign up to set email alerts
|

Floral resource pulse decreases bumble bee foraging trip duration in central Wisconsin agroecosystem

Abstract: Cranberry bloom represents a significant pulse of floral resources – increasing floral area by 400% within a 2‐km landscape, relative to the area of ambient (non‐crop) floral area before bloom. Bumble bee foraging trip duration decreases by 18% in synchrony with cranberry bloom, number of trips increase by 25%, and returning bumble bee foragers carry cranberry pollen almost exclusively. Foraging responses are consistent across individuals, colonies, landscape types (high versus low natural area), and both year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 59 publications
2
19
0
Order By: Relevance
“…Mass‐flowering floral displays, including crops such as canola and sunflower, are known to be important foraging resources for eusocial pollinators, especially bumble bees (Hemberger & Gratton, 2018; Rundlöf et al, 2014; Westphal et al, 2009). We found that large Phacelia flower plantings were used by foraging bumble bees in this agricultural landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Mass‐flowering floral displays, including crops such as canola and sunflower, are known to be important foraging resources for eusocial pollinators, especially bumble bees (Hemberger & Gratton, 2018; Rundlöf et al, 2014; Westphal et al, 2009). We found that large Phacelia flower plantings were used by foraging bumble bees in this agricultural landscape.…”
Section: Discussionmentioning
confidence: 99%
“…This relative benefit may explain why a land cover that is described as pollinator-supportive in one region is not necessarily found to be pollinator-supportive in another region. For example, while intensive row crop monocultures are considered to be detrimental to pollinators in some contexts [6,15], mass-blooming monocultural crops can provide short-term flowering pulses [20,21], and thus the effect on pollinator populations depends upon overall landscape composition [22]. Likewise, agricultural management approaches that integrate flowering plants into the crop rows or field margins either by planting or by allowing volunteer plants to grow, can increase the pollinator attractiveness of farms [23].…”
Section: Introductionmentioning
confidence: 99%
“…and optical tags RFID uses smaller tags than those for radar, but tags must be read by readers within a subcentimeter range (Reynolds and Riley 2002, Silcox et al 2011, Nunes-Silva et al 2018, making it infeasible for continual long-range detection like radar tracking. It has most successfully been used to follow workers entering and leaving captive nests or feeders (Gill et al 2012, Hemberger and Gratton 2018, Malfi et al 2018 but not for direct observations across a large landscape array. For example, it can be used to measure time away from a colony for many individuals, yielding an estimate of the time spent foraging and a proxy for landscape-scale foraging effort (Hemberger and Gratton 2018; for an example without RFID, see Westphal et al, 2006) and colony-wide activity patterns and potential task allocation (Kerr et al 2019).…”
Section: Radio-frequency Identification (Rfid)mentioning
confidence: 99%
“…We encourage practitioners to use available methods to investigate differences between individuals, castes, age classes, body sizes, or differing contexts. More recent studies have begun to reveal the ontogeny of forager flight a n d d i f f e r e n c e s b e t w e e n i n d i v i d u a l s (Woodgate et al 2016), as well as colonylevel variability in foraging effort as the resource landscape changes (Hemberger andGratton 2018, Pope andJha 2018). Continued efforts are likely to reveal more about the plasticity and flexibility of movement among life stages, allowing us to understand the impacts of habitat fragmentation, agrochemical exposure, changing climate, and resource availability on the movement patterns and population viability of bumble bees.…”
Section: Future Directionsmentioning
confidence: 99%